Variability of daily precipitation on the caribbean coast of Costa Rica - Quesada Quesada, Marvin Elí (2020)
This study analyzes daily rainfall to investigate its interannual variability at Limón, located in the Caribbean coast of Costa Rica. The station is the only one along the Caribbean coast with a large record (80 years) and it is very hard to find in the surrender with a good quality in order to complete detailed analysis. The Caribbean coast and its susceptibility to precipitation variability has been studied less extensively than the Pacific coast and populated regions of the Central Tectonic Depression, yet it supports nationally important agriculture. Seven variables related to the magnitude and frequency of daily rainfall each month are extracted: monthly totals, probability of a day with rain, mean size of daily measurable rains, probability of daily totals exceeding, 10 mm, 20 mm and 30 mm, and the maximum daily rainfall total. Unlike much of the rest of the country, the Warm phase of El Niño-Southern Oscillation brings increases in most of these variables during most of the year. Only during September through December, is this signal effaced or even reversed. The principal cause of these changes appears to be the intensification of the Caribbean Low-Level Jet (CLLJ) during Warm phase events, not ably during the boreal summer. This increases convergence and enhances orographic rainfall. However, the slight reversal of this pattern in the boreal winter, despite an enhanced CLLJ, implies a more complex relationship between ENSO and the outbreaks of cold air from North America, which are responsible for much of the rain at that time of year.